Pengaruh Komunikasi, Disiplin Kerja, dan Motivasi Kerja terhadap Kinerja Karyawan pada PT Kharisma Karya Kartika - Ely Hopidah Nasution; M. Khoiri (Departement of Mathematics Education, 2023)
PT Kharisma Karya Kartika is a frozen meat processing company that has exported its products to various countries. Employees of PT Kharisma Karya Kartika are important human resources for the progress of a company. This study aims to determine the effect of communication, work discipline, and motivation on employee performance. The method used is a qualitative method with a literature study approach. Data collection ie. by searching for secondary data through books, journals, articles, or websites that are available and reliable. The results showed that communication, work discipline and motivation have a significant effect on employee performance. Employee performance is increasing along with motivation and work discipline and effective communication